Particle physics : a very short introduction - Close, F. E. (Very short introductions ;, 2004)
Beginning with a guide to what matter is and what it is made of this book discusses everything from quarks and electrons to exotic matter and antimatter. The author concludes by speculating as to the number of dimensions that might be in the universe, and what the next 50 years of research might uncover.